EFEKTIVITAS PROGRAM KANG PISMAN DI KOTA BANDUNG DALAM MENINGKATKAN TANGGUNG JAWAB WARGA NEGARA (CIVIC RESPONSIBILITY) TERHADAP LINGKUNGAN (Studi Kasus di Kelurahan Gumuruh, Kecamatan Batununggal, Kota Bandung) - Desy Nur Annisa, - (2020)
The purpose in this research for discover effectiveness Kang Pisman program in the city of Bandung to improving citizens' responsibility towards their environment. The method in this research use qualitative and quantitative methods in the case studies at the Gumuruh Village, Batununggal District, Bandung City. Data collection techniques implemented by observation, interviews, questionnaires and documentation studies. The result in this research refer the implementation of the Kang Pisman program in the Gumuruh Village was implemented through various activities starting from planning, conducting socialization, and implementing programs namely reduce of producing waste, sorting out waste, until utilize the waste from waste sources so it can bring positive impact with decreasing amount of waste at the garbage dump of Gumuruh Village. The obstacles that arise in the implementation of the Kang Pisman program in Gumuruh Village there are less of awareness from several people to the environment, lack of community knowledge of the program, and inadequate to processing organic waste facilities. The means to carry these obstacles are doing socialization with sustainability, adapt and gather citizens to carry out GPS (Garbage Collection Movement), as well as putting up banners in several of places to remind citizen for treat the waste properly. Based on the research data, it is shows that the effectiveness of the Kang Pisman program implemented in the Village Gumuruh has a positive impact on the level responsibility of citizens in their environment. Therefore, the main focus in this research is about the "Effectiveness Kang Pisman Program in Bandung in improving the Responsibility of Citizens (Civic Responsibility) on the Environment".